New Boric Acid Derivative with Some of Its Complexes and Study the Biological and Anticancer Activity - Abdullah Majeed, Alaa; Mohammed Noori, Asmaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
A new ligand (5-(2-benzamido-N-methylacetamido)-4-((3,4,5-trimethoxycyclohexa-1,3-dien-1-yl) methyl) pyrimidine-2-yl) amino)boric acid was synthesized by the reaction of trimethoprim amide derivative with boric acid, as well as its metal complexes with Co (II), Ni (II), and Pt (IV). Spectral methods such as Fourier transform infrared spectroscopy, ultraviolet-visible spectroscopy, and proton nuclear magnetic resonance (1H-NMR) spectra, along with thermal analysis (TG/DTA), elemental analysis (CHN), and melting point, were used to characterize the synthesized compounds. This study conducted additional examinations for metal complexes, including molar conductivity, magnetic susceptibility, chloride, and metal content. All synthesized complexes have octahedral geometry; cobalt and nickel complexes are nonelectrolytes, while platinum complexes are electrolytic. This study tested all the synthesized compounds as antibacterial and antifungal agents against Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albican. Additionally, this study tested the new ligand and its platinum complexes as anticancer agents against adenocarcinoma human cells (A549). Thus study have achieved positive outcomes for every complex’s antibacterial, antifungal, and anticancer properties.